Doctoral students' research motivation and outcomes in China: training environment moderation - Huang, Siqi; Yang, Cheng-Cheng (Cogent education, 2024)
The exploration of factors influencing the output of doctoral research results is meaningful for higher education management. This study's purpose lay in investigating the influence of motivation and training environment on doctoral students' research outcomes in the Chinese province of Sichuan. The study aimed to explore whether environment moderates the relation of motivation to research outcome. Through convenience sampling, we selected six universities in Sichuan Province, China, obtaining 646 valid responses. We used hierarchical regression analysis in this research. Results indicated that research motivation significantly and positively influences research outcomes among Sichuan's doctoral students. Furthermore, environment significantly, positively moderates the relation of motivation to outcome. This study unveils novel variable relationships, notably identifying a significant positive moderating effect of the research training environment on the relationship between research motivation and outcomes. Additionally, we have developed locally contextualized scales for research training environment and research outcomes in China. This study holds certain significance for guiding the research output of doctoral students. This study explores the relationships between research motivation, research training environment, and research outcomes among doctoral students in Sichuan, China. Understanding these dynamics is crucial as it sheds light on how educational institutions can better support doctoral candidates to achieve higher academic productivity and success. By identifying key factors that influence doctoral students' research performance, this research provides valuable insights for universities aiming to enhance their training programs and foster a more effective and supportive academic environment.